Representation of women in computer game prince of persia - Cetin, Derya (Elsevier Science Bv, 2015)
The stories of the popular video games include narrations like movies and other various media contents, and of course those contents are ideological. With this study, we are intending to, by making use of the feminist film theory, compare the 1989 and 2003 versions of Prince of Persia in the sense of representation of women. At the first version the story ends with the traditional patriarchal ends; however at the second version the Princess makes her own way. Within that scope it can be asserted that The Prince of Persia: The Sands of Time, despite being a popular text, includes a cracked-line that may be useful for oppositional readings. (C) 2015 Published by Elsevier Ltd.
International Educational Technology Conference IETC -- SEP 03-05, 2014 -- Chicago, IL
Keywords: Computer games; women representation; feminist theory